(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2012)
According to Gottfried Boehm and W.J.T. Mitchell the science of images is not yet ready to write its own history. However, the present paper tries to focus and discuss some controversial points that we have to take as preliminary ontological and epistemological conditions for any kind of Bildwissenschaft: the close relationships between definition and identification of images, their theoretical and historical identity, the cognitive status of their perception and content, the epistemic dimension of image experience.